Reverberation chamber for electromagnetic compatibility testing of electric thrusters - Kiefer, Felix; Holste, Kristof; Klar, Peter J.; Rover, Yannik; Probst, Uwe; Volkmar, Chris; Justus Liebig University Giessen (My University, 2023)
The need for electromagnetic compatibility (EMC) of electrical devices on satellites increases dramatically as the number of satellites is rapidly growing and the density of electrical devices on the satellite increases due to their miniaturization. Thus, EMC of the electric propulsion system becomes an important issue for a safe and reliable operation of the satellite. In particular, this also concerns the electric propulsion system. Since electric thrusters usually need to be operated in vacuum, dedicated facilities are required to assess their EMC. Here, we present how a common cylindrical vacuum vessel can be converted into a reverberation chamber suitable for EMC pre-compliance testing of electric thrusters. We describe and validate its operation principle and discuss its limitations. Finally, we show first measurement results of radiated emission measurements of a thruster and compare those with data obtained for the same thruster in a semi-anechoic chamber where the thruster is operated inside a metal-free vessel and fires into a larger vacuum chamber outside the semi-anechoic chamber.
Keywords: Electromagnetic interference testing; Electric propulsion; Electromagnetic compatibility; Reverberation chamber; Semi-anechoic chamber; ddc:530